Applications of the Near Attack Conformation (NAC) approach in the search for Acetylcholinesterase reactivators - França, Tanos Celmar Costa; Valle da Silva, Jorge Alberto; Dos Santos, Marcelo Carneiro; Cavalcante, Samir Frontino de Almeida; Kuca, Kamil (Chemico-biological interactions, 2023)
The Near Attack Conformation (NAC) approach states that the efficiency of an enzyme-catalyzed reaction depends on the prior attainment of optimal conditions for substrate atom organization and positioning for bond formation. These conditions are prerequisites for the transition state (TS) in which the involved atoms are within the van der Waals range of contact and positioned at an angle similar to that achieved after bond formation. The successful application of this approach to investigate the reactivation mechanism of acetylcholinesterase inhibited by nerve agents has contributed to a better understanding of this mechanism and demonstrated consistent corroboration with experimental data. In this article, we summarize the accomplishments achieved thus far and outline future perspectives.
Keywords: acetylcholinesterasa; reaktivátory cholinesterasy; Oximes; cholinesterasové inhibitory; Near Attack Conformation (NAC); Acetylcholinesterase; Cholinesterase Inhibitors; AChE reactivators; oximy; Cholinesterase Reactivators